Differences In The Effectiveness Of Massage Tuina And Grant Aromatherapy Oil Lemongrass (Cymbopogonnardus) In Overcoming Difficulties Eating In Children In The Work Area Health Balowerti Kediri City - Saidah, Halimatus; Dewi, Rahma Kusuma (STRADA : Jurnal Ilmiah Kesehatan, 2020)
In Indonesia in 2012 there were around 53% of children under the age of 5 suffering from malnutrition due to a lack of food to meet their daily nutritional needs (Ministry of Health, 2012). Giving Lemongrass Oil Aromatherapy (Cymbogon Nardus) and Tuina Massage can be used as alternative treatments to overcome feeding difficulties in toddlers. The purpose of this study was to determine the difference in the effectiveness of <span style="display: inline !important; float: none; background-color: transparent; color: #000000; cursor: text; font-family: ’Noto Sans’,Arial,Helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Lemongrass Oil Aromatherapy and Tuina Massage in overcoming feeding difficulties in toddlers. The research design was Two Group Pre Test Post Test Design with a population of children under five who had difficulty eating totaling 32 respondents, l data using Wilcoxon and different tests using Man. Whitney. The results showed that there is a difference between giving lemongrass oil aromatherapy with tuina massage in overcoming feeding difficulties in toddlers (P_Value = 0,0056)